Effects of Islamic entrepreneurship mind programming on entrepreneurial performance through entrepreneurial motivation - Abdullah, Moha Asri; Kedah, Zulkarnain; Anwar, Md. Aftab (Inderscience Publishers, 2015)
This study attempts to identify the attributes and essential elements of Islamic entrepreneurial mind programming and to utilise a contemporary psychological method to evaluate consciousness that enhance entrepreneurial performance through entrepreneurial motivation among the entrepreneurs in Malaysia. Emphasis on entrepreneurial aspects of Islam has not been given enough attention in the field of entrepreneurship literature which might be an important component for Muslims entrepreneurial motivation and performance. A survey data of 201 respondents were used to test the research model using structural equation modelling (SEM). The study represents a significant positive relationship between Islamic entrepreneurial mind programming and entrepreneurial performance mediated by entrepreneurial motivation. The findings of the results confirm that Islamic entrepreneurial mind programming is an important factor among other factors that have influenced over entrepreneurial motivation. The outcome of the study will help the training and development authorities to take necessary steps to outline a new and productive content for potential entrepreneurial development.